The use of a medical application improves the diagnosis of acute kidney injury: A pre-post study - Gaspar, Andrea; Iturricha-Cáceres, Maria F.; Macedo, Etienne; Mehta, Ravindra L.; Claure-Del Granado, Rolando (Frontiers in Medicine, 2022)
Background: The use of mobile devices by health care providers has transformed many aspects of clinical practice. Mobile devices and medical applications provide many benefits, perhaps most significantly increased access to point-of-care (POC) tools, which has been shown to support better clinical decision making and improved patient outcomes. In this study, we tested the hypothesis that the use of an app specifically designed for recognition and management of AKI will help health care providers better identify and classify AKI. Methods: We included 20 AKI cases from our center Global Snapshot study report. 20 clinical vignettes of these patients including baseline serum creatinine (sCr) and a second sCr that was measure within seven days were presented to 50 last year medical students. They were asked two simple questions: 1) To identify the development of AKI and 2) To classify the stage of AKI before and after providing them with an app that was developed for early identification, classification and management of AKI (IRA SLANH app, Island of the Moon® V.1, 2014; Cochabamba-Bolivia). We analyzed if the use of this medical app could improve correct identification and stage classification of AKI. Results: Before the IRA SLANH app was introduced, the mean number of correctly identified cases of AKI was 14.7±4.7 with a minimum of 3 and a maximum of 20. The stage of AKI was correctly identified in only 6.7±4.4 of the cases. After the app was introduced, the number of correctly identified cases of AKI was 20. AKI stage was also correctly classified in all 20 cases. Before the medical app was introduced to the medical students, only 22% of them were able to correctly identify all AKI cases, and 0% of them could correctly classify all AKI cases. Conclusions: Many medical applications have been developed and are widely used by health care providers. Medical applications are useful tools in the practice of evidence-based medicine at the POC. Their use could play a very important role in early identification and classification of AKI, potentially allowing for earlier intervention with preventive and treatment strategies to reverse kidney injury and improve recovery.